Anesthetic Management in Ventriculoperitoneal Shunt Insertion in Preterm Congenital Hydrocephalus - Kashif, Sanum (Pakistan Armed Forces Medical Journal, 2025)
Abstract Neonatal hydrocephalus is a multifactorial disorder and is a common cause of death among preterm babies. Prematurity is a challenge for anesthetists as far as major surgery is concerned. In the development of neonatal brain, maintenance of normal intracranial pressure is essential by timely intervention in neonatal hydrocephalus. We share the case of a 20-day-old premature baby, delivered at 32 weeks of gestation as twins with congenital hydrocephalus, presented with fever and lethargy and after made diagnosis, treated on the lines of neonatal sepsis and due to gross hydrocephalus, ventriculoperitoneal shunt insertion was planned under general anesthesia.